Exploring the Cholesterol-Modifying Abilities of Lactobacilli Cells in Digestive Models and Dairy Products - Małgorzata Ziarno; Dorota Zaręba; Iwona Ścibisz; Mariola Kozłowska (Microorganisms, 2023)
This study aimed to investigate the ability of lactic acid bacteria to remove cholesterol in simulated gastric and intestinal fluids. The findings showed that the amount of cholesterol removed was dependent on the biomass, viability, and bacterial strain. Some cholesterol binding was stable and not released during gastrointestinal transit. The presence of cholesterol affected the fatty acid profile of bacterial cells, potentially influencing their metabolism and functioning. However, adding cholesterol did not significantly impact the survival of lactic acid bacteria during gastrointestinal transit. Storage time, passage, and bacterial culture type did not show significant effects on cholesterol content in fermented dairy products. Variations in cell survival were observed among lactic acid bacteria strains in simulated gastric and intestinal fluids, depending on the environment. Higher milk protein content was found to be more protective for bacterial cells during gastrointestinal transit than fat content. Future research should aim to better understand the impact of cholesterol on lactic acid bacteria metabolism and identify potential health benefits.